Malaysian army veterans’ outlay and discernment towards financial aid / Mohd Zahid Laton and Harlina Yunus @ Junor - Laton, Mohd Zahid; Yunus @ Junor, Harlina (Universiti Teknologi MARA Cawangan Pahang, 2013)
In the announcement of the Malaysian Budget 2013, the Prime Minister proposed a compensation in the form of a financial aid to the army veterans who did not opt for the pension scheme after retiring from the military services. The amount of compensation was one thousand ringgit Malaysia and disbursed beginning January 2013. The one-off payment scheme was called “Sumbangan Veteran Tidak Berpencen 1Malaysia” (SVTB1Malaysia). This study focuses on the purpose of the money spent by the army veterans and the types of outlay whether for individual, family, or other purposes, and also their discernment towards the reward given. The population of this study was the army veterans who live in the rural part of the East Coast of Malaysia. The study was conducted during the distribution of the SVTB1Malaysia form.